Bidirectional Risk Association Between Hidradenitis Suppurativa and Inflammatory Bowel Disease - Louise Lönndahl; Maria Najeeb; Hassan Killasli; Lennart Emtestam; Ralf J. Ludwig; Philip Curman (Acta Dermato-Venereologica)
Hidradenitis suppurativa is an inflammatory skin disease of the pilosebaceous unit encompassing painful, recurrent, and malodorous abscesses, inflammatory nodules, dermal sinus tracts, and cicatrices. Hidradenitis suppurativa has been linked to several comorbidities, including inflammatory bowel disease, though evidence is limited by small sample sizes and possible bidirectional associations remain uncertain. A large-scale, propensity-score matched retrospective cohort study was performed using the TriNetX platform to investigate bidirectional risks between hidradenitis suppurativa and inflammatory bowel disease. Data included over 200,000 hidradenitis suppurativa patients and 3.3 million inflammatory bowel disease patients. Hidradenitis suppurativa was associated with a 36% increased risk of developing any inflammatory bowel disease diagnosis within 5 years of diagnosis (hazard ratio [HR] 1.356, confidence interval [CI] 1.313–1.401), with the highest risk of Crohn’s disease (HR 2.501, CI 2.209–2.832), followed by ulcerative colitis (UC) (HR 1.722, CI 1.536–1.930), and other/unspecified inflammatory bowel disease (HR 1.349, CI 1.306–1.394). Conversely, individuals with any inflammatory bowel disease diagnosis had a 31% increased risk of developing hidradenitis suppurativa (HR 1.313, CI 1.274–1.353), with Crohn’s disease showing the strongest association (HR 2.441, CI 2.242–2.658), followed by UC (HR 1.493, CI 1.358–1.642). These findings highlight the bidirectional risk relationship between hidradenitis suppurativa and inflammatory bowel disease, demonstrating that the likelihood of developing either condition is significantly elevated in patients already diagnosed with the other.